Study on the Self–Growth of the Internet Communication System - Yun-Feng Xia (tripleC: Communication, Capitalism & Critique)
In this essay, I mainly discuss the self-organizing property of the Internet communication system. As an important part of the human information communication system, Internet communication has progressively become a system with large scale, complex constructions, and perfect functions through the complicated interactions among many sub-systems and their elements. In this process, which is mainly promoted by Internet users, the self-growth of the Internet communica- tion system not only increases the amount of its sub-systems and its elements, it also strengthens its constructions and functions. At the same time, the self-growth of the Internet communication system indicates that the system is an evolving system with self-organizing property.